Adverse Drug Reactions pattern in a tertiary level teaching hospital: A Retrospective Study - Gupta, Anita; Kaur, Anjleen; Shukla, Prashant; Chhabra, Hema (Indian Journal of Pharmacy Practice)
Objective: The objective of the study was to assess the pattern of adverse drug reactions (ADRs) along with the severity and causality assessment of the ADRs in the local population. Method: This was an observational and retrospective study. A total of 288 adverse drug reactions were reported from 175 patients of the outpatient and inpatient department of various clinical departments of Rajindra Hospital, Government Medical College, Patiala, Punjab. The ADRs were collected duringNovember 2015- August 2016. Results: The mean age of the patients was 43.14 (± 2.27) years. Gender distribution of the patients showed that there were 67 (38.28%) female and 108 (61.7%) male patients indicating male preponderance. Out of 288 ADRs, the majority of ADRs were related to the skin and appendages (26.04%) closely followed by gastrointestinal disorders (24.3%). Other ADRs were related to Central nervous system (12.15%), respiratory system (7.29%), cardiovascular system (6.94%) and others (23.2%). Using Naranjo’s causality assessment scale, there were 9 definite, 131 probable, 136 possible and 12 doubtful/ unlikely causality of the ADRs with the suspected offending drug. Using Hartwig and Siegel scale of severity of ADR, it was found that there were 230 mild (79.86%), 52 moderate (18.05%) and 6 severe (2.08%) ADRs. Conclusion: The process of pharmacovigilance is a continuous one so as to detect even the rare ADRs.
Keywords: Adverse drug reactions (ADRs); Spontaneous reporting; Pharmacovigilance; Naranjo’s scale; Hartwig and Siegel scale